2016
DOI: 10.3329/bjar.v41i3.29717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of osmopriming on germination of rice seed

Abstract: The experiment was conducted at the Seed Laboratory, Department of Agronomy, Bangladesh Agricultural University, Mymensingh during the period from September to October, 2011 to study the effect of chemical priming of seed on germination and growth of rice seedling cv. BRRI dhan 29. Seeds were soaked in 3% and 5% solutions of CaCl 2 , ZnSO 4 and KCl for 24, 30, 36, 42, 48, 54, 60 hours, respectively. A control was maintained where seeds were subjected to no priming treatment. The experiment was laid out in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Several other researchers had also reported the result in the same direction as found in the present study. Hasan et al, 2016 also concluded that paddy seed primed with ZnSO 4 (3.0 %) for 30 hours, resulted in highest germination percentage and the lowest mean germination time. Marthandan et al, 2017 reported that undried rice seeds at high moisture stores under cold storage is found to be best as compared to ambient storage condition.…”
Section: Iron Content In Seed (Fe; Ppm)mentioning
confidence: 95%
“…Several other researchers had also reported the result in the same direction as found in the present study. Hasan et al, 2016 also concluded that paddy seed primed with ZnSO 4 (3.0 %) for 30 hours, resulted in highest germination percentage and the lowest mean germination time. Marthandan et al, 2017 reported that undried rice seeds at high moisture stores under cold storage is found to be best as compared to ambient storage condition.…”
Section: Iron Content In Seed (Fe; Ppm)mentioning
confidence: 95%
“…• Hasan et al (2016) while studying on the osmopriming for paddy seed reported that priming the seeds with 3% ZnSO 4 and 5% KCl for different durations had significant influence on germination percentage, growth parameters (root length, root dry weight) and less germination time. The priming of rice seeds with KNO 3 also influenced significantly the yield of paddy.…”
Section: Uses In Cropsmentioning
confidence: 99%
“…Batool et al, (2015) [45] Osmopriming 1.Highest germination percentage were found prime with CaCl2, ZnSO4 and KCl 2. Improve field crop establishment in 1% KNO3 salt solution Hasan et al, (2016) [46] Singh et al, (2012) [47] Osmohardening 1. Osmo-hardeningr with Vitamin C increase germination , vigor index, shoot and root lengths Mamun et al, (2018) [48] 2.…”
Section: Manifestationmentioning
confidence: 99%